The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.48185/spda.v3i1.483
|View full text |Cite
|
Sign up to set email alerts
|

Evidentiality through reported speech: Pragma-linguistic factors affecting its reliability

Abstract: This study focuses on reportative evidential that contains statements of a specific and commonly known individual with interlocutors regarding the quality of evidence s/he claimed to have, his/her trustworthiness as a person, linguistic markers, turn designs, emotional state, epistemic authority, as factors which determine the reliability of information vouched through reported speech. We collected 28 conversations in which informants were asked to convey information derived from someone well or weakly known. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
0
0
Order By: Relevance
“…Rather than focusing on the devices' grammaticalisation or semantic properties, several recent studies have revealed the pragmatic effects involved in the use of so-called 'markers of belief' (Carretero & Zamorano-Mansilla, 2019;Gonzalez-Vazquez, 2021;Jahiu, 2022;Marín Arrese, 2015;Ruskan, 2017). Another example is Geng and Wharton's (2019) qualitative analysis, which looked into how student writers engage with findings obtained in previous studies in the discussion section of their thesis.…”
Section: The System Of Engagementmentioning
confidence: 99%
“…Rather than focusing on the devices' grammaticalisation or semantic properties, several recent studies have revealed the pragmatic effects involved in the use of so-called 'markers of belief' (Carretero & Zamorano-Mansilla, 2019;Gonzalez-Vazquez, 2021;Jahiu, 2022;Marín Arrese, 2015;Ruskan, 2017). Another example is Geng and Wharton's (2019) qualitative analysis, which looked into how student writers engage with findings obtained in previous studies in the discussion section of their thesis.…”
Section: The System Of Engagementmentioning
confidence: 99%